1999
DOI: 10.1016/s0014-5793(99)01196-5
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum fluoride inhibits phospholipase D activation by a GTP‐binding protein‐independent mechanism

Abstract: Aluminum fluoride (AlF 3 4 ) inhibited guanine nucleotide-activated phospholipase D (PLD) in rat submandibular gland cell-free lysates in a concentration-dependent response. This effect was consistent in permeabilized cells with endogenous phospholipid PLD substrates. Inhibition was not caused by either fluoride or aluminum alone and was reversed by aluminum chelation. Inhibition of PLD by aluminum fluoride was not mediated by cAMP, phosphatases 1, 2A or 2B, or phosphatidate phosphohydrolase. AlF 3 4 had a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…For example, it has been suggested that the AIF-sensitive component in vesicle transport may not be a GTP-binding protein (21). Indeed, AlF 4 is known to inhibit other phosphoryl transfer reactions involved in vesicle transport, such as phospholipase D activity (27,34). Thus, AlF 4 may provide a means of further dissecting this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that the AIF-sensitive component in vesicle transport may not be a GTP-binding protein (21). Indeed, AlF 4 is known to inhibit other phosphoryl transfer reactions involved in vesicle transport, such as phospholipase D activity (27,34). Thus, AlF 4 may provide a means of further dissecting this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, both mechanisms would lead to increased tyrosyl phosphorylation and to subsequent activation of the mitogenactivated protein (MAP) kinase pathway, although other signaling pathways cannot be excluded [12,32]. For instance, on one hand fluoride (5-10 mM, 95-190 mg/l) has been observed to inhibit directly, in rat skeletal muscle, the tyrosine kinase activity of the insulin receptor [79], and aluminum fluoride (3 mM, 57 mg/l fluoride) inhibits phospholipase D (PLD) in rat submandibular cells by a G protein-independent mechanism, which could be a regulatory protein of PLD or PLD itself [80]. On the other hand, in C6 rat glioma cells, sodium fluoride (10 mM, 190 mg/l fluoride) activated Gs or inhibited Gi to increase the cAMP concentration [81,82] and enhanced the cGMP generation via calcium/calmodulin-and nitric oxide synthase-dependent pathways [82], and the activation of G proteins by fluoride (1-20 mM, 19-380 mg/l) in smooth muscle cells initiated a series of events, including calcium mobilization, phospholipase C activation and protein kinase C activation [83,84].…”
Section: Activation Of G Proteins and Kinases And Inhibition Of Phospmentioning
confidence: 99%
“…More specifically, AlF 4 has been found to inhibit GTP--S-induced PLD activation in rat submandibular gland acinar cells. Such AlF 4 inhibitory effect was confirmed in permeabilized cells in a concentration-dependent manner [95]. It is known that PLD stimulation with ARF/GTP--S involves ARF translocation from cytosol to membranes [96].…”
Section: Mysterious Inhibitorsmentioning
confidence: 77%
“…In this case, since AlF 4 inhibited PLD in the membrane fraction alone, a non GTP-binding membraneassociated target is proposed. This target could be a PLD regulatory protein, or the enzyme itself [95]. Since fatty acid (oleate)-sensitive PLD, which is not guanine nucleotidedependent, was also powerfully inhibited by AlF 4 in a concentration-dependent way, it is excluded a G-proteins involvement in the mechanism through which AlF 4 inhibits PLD activity.…”
Section: Mysterious Inhibitorsmentioning
confidence: 99%